Characterization of the Complete Mitochondrial Genome of Drabescus ineffectus and Roxasellana stellata (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) and Their Phylogenetic Implications - Deliang Xu; Tinghao Yu; Yalin Zhang (Insects, 2020)
To explore the mitogenome characteristics and shed light on the phylogenetic relationships and molecular evolution of Drabescini species, we sequenced and analyzed the complete mitochondrial genome of two species including Drabescus ineffectus and Roxasellana stellata. The complete mitogenomes of D. ineffectus and R. stellata are circular, closed and double-stranded molecules with a total length of 15744 bp and 15361 bp, respectively. These two newly sequenced mitogenomes contain the typical 37 genes. Most protein-coding genes (PCGs) began with the start codon ATN and terminated with the terminal codon TAA or TAG, with an exception of a special initiation codon of ND5, which started with TTG, and an incomplete stop codon T-- was found in the Cytb, COX2, ND1 and ND4. All tRNAs could be folded into the canonical cloverleaf secondary structure except for the trnS1, which lacks the DHU arm and is replaced by a simple loop. The multiple tandem repeat units were found in A + T-control region. The sliding window, Ka/Ks and genetic distance analyses indicated that the ATP8 presents a high variability and fast evolutionary rate compared to other PCGs. Phylogenetic analyses based on three different datasets (PCG123, PCG12R and AA) using both Bayesian inference (BI) and maximum likelihood (ML) methods showed strong support for the monophyly of Drabescini.